Major, trace element and Sr-isotope characterization of the Samothraki tertiary volcanic rocks, NE Aegean - VLAHOU, M.; CHRISTOFIDES, G.; ELEFTHERIADIS, G.; PINARELLI, L.; KASSOLI-FOURNARAKI, A. (Bulletin of the Geological Society of Greece, 2001)
Tertiary volcanic rocks of the Samothraki Island were found to show a wide range of composition. Two series have been distinguished showing diverging trends both in major and in trace element diagrams. Sr-isotope data show even more pronounced grouping of the two series thus reinforcing the suggestion of diverse evolutionary processes. A possible origin from either an enriched mantle source for the old volcanic series and mantle plus crust for the young volcanic rock series is suggested. Fractional crystallization or any other closed system process cannot account for the geochemical and isotopie variations seen witin the rock series. More complex processes must be responsible for their evolution history.